2008
DOI: 10.1590/s0034-71672008000600015
|View full text |Cite
|
Sign up to set email alerts
|

Correntes de pensamento nacionais sobre sistematização da assistência de enfermagem

Abstract: RESUMO RESUMO RESUMO RESUMO RESUMO Trata-se de uma pesquisa que tem por objetivo analisar a produção bibliográfica sobre a sistematização da assistência de enfermagem a fim de discutir conceitos associados ao tema. Foram analisados livros e artigos nacionais publicados na base de dados da Biblioteca Virtual em Saúde, Medline, Lilacs e Scielo, no período de janeiro de 2000 a janeiro de 2008. Formam analisados 11 artigos, tendo sido identificadas três correntes de pensamento distintas para definição de termos as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
28

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 10 publications
0
25
0
28
Order By: Relevance
“…Thus, this process is the technological tool that supports the intellectual activity of nurses and provides the guidelines they need to adopt a given clinical and therapeutic judgement style. This instrument is the essence of today's nursing practice (4) . With the use of this methodology, some nursing classification systems have been developed to standardise the language between nurses and the nursing staff.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this process is the technological tool that supports the intellectual activity of nurses and provides the guidelines they need to adopt a given clinical and therapeutic judgement style. This instrument is the essence of today's nursing practice (4) . With the use of this methodology, some nursing classification systems have been developed to standardise the language between nurses and the nursing staff.…”
Section: Introductionmentioning
confidence: 99%
“…Resolution COFEN No. 358/2009 emphasises the need to apply the SAE in the different nursing work scenarios and that nurses -as part of their work activities -should be responsible for implementing, planning, organising and assessing the whole process (4) . However, a study conducted in obstetrics services in the state of Paraíba showed that some of the factors that hamper this operationalisation singled out by the nurses were lack of a theoretical foundation regarding the nursing process that leads to deficiencies in the design of data collection instruments, in the establishment of incorrect or incomplete diagnoses for specific sectors, and in the construction of nursing interventions that are different to the needs of parturition and clinical problems in high-risk pregnancies; the lack of credibility of nursing technicians regarding the SAE; the workload of nurses; and the lack of interest of managers to implement SAE (7) .…”
Section: Introductionmentioning
confidence: 99%
“…A segunda corrente trata a MAE e o PE como sendo termos equivalentes. E, uma terceira corrente defende que os três termos são sinônimos 11 .…”
Section: Introductionunclassified
“…O registro deve ser realizado formalmente em um instrumento que apresente o resumo dos dados coletados durante a consulta de enfermagem, os diagnós-ticos de enfermagem identificados a partir da consulta, as ações de enfermagem realizadas e os resultados alcançados (9) . (10) . A CIPE ® é um sistema de linguagem de enfermagem, unificado e universal, que integra as diversas classificações desenvolvidas ao longo do tempo, facilitando a melhoria da assistência ao cliente e permitindo a visibilidade da contribuição do enfermeiro na equipe multiprofissional.…”
Section: Introductionunclassified